KORBAN “TUHAN-TUHAN” DIGITAL: GARAPAN MASA DEPAN PENYULUHAN PEMBANGUNAN 4.0 - Iwan Setiawan; Siska Rasiska; Dika Supyandi (Lampung University, 2019)
The 4.0 Industrial Revolution which was marked by the birth of smart technology and machinery, automation (robotic), artificial intelligence and IoT encouraged disruptive change, which was different from the industrial revolution 1.0-3.0. A critical perspective considers that humans will become highly dependent on smart technology. There are anecdotes, intelligent technology has become a